Isotope-dilution mass spectrometry for exact quantification of noncanonical DNA nucleosides. Issue 1 (January 2019) - Traube, Franziska; Schiffers, Sarah; Iwan, Katharina; Kellner, Stefanie; Spada, Fabio; Müller, Markus; Carell, Thomas
Abstract DNA contains not only canonical nucleotides but also a variety of modifications of the bases. In particular, cytosine and adenine are frequently modified. Determination of the exact quantity of these noncanonical bases can contribute to the characterization of the state of a biological system, e.g., determination of disease or developmental processes, and is therefore extremely important. Here, we present a workflow that includes detailed description of critical sample preparation steps and important aspects of mass spectrometry analysis and validation. In this protocol, extraction and digestion of DNA by an optimized spin-column and enzyme–based method are described. Isotopically labeled standards are added in the course of DNA digestion, which allows exact quantification by isotope dilution mass spectrometry. To overcome the major bottleneck of such analyses, we developed a short ( 14-min-per-sample) ultra-HPLC (UHPLC) and triple quadrupole mass spectrometric (QQQ-MS) method. Easy calculation of the modification abundance in the genome is possible with the provided evaluation sheets. Compared to alternative methods, the quantification procedure presented here allows rapid, ultrasensitive (low femtomole range) and highly reproducible quantification of different nucleosides in parallel. Including sample preparation and evaluation, quantification of DNA modifications can be achieved in less than a week. In addition to canonical nucleotides, DNA contains various modified bases that contribute to the developmental and disease state of the organism. UHPLC–MS/MS with isotopically labeled standards is used in this protocol to quantify modified bases.